CRM SYSTEM USING PROCUREMENT LOGISTICS METHODS AND IMPLEMENTION OF ABC AND XYZ CLASSIFICATION METHODS IN THE C# PROGRAMMING LANGUAGE - Savchuk, A.О.; Kulakovska, I.V. (SWorld-Ger Conference proceedings, 2024)
This article presents the design and development of a Customer Relationship Management (CRM) system that integrates procurement logistics methods with the implementation of ABC and XYZ classification techniques. Using C# and WinForms in Visual Studio, the